The effects of land conversion on the aricultural economy and development of selected towns of Pampanga - Angeles, Daryl; Gomez, Precious Joy; Lacanilao, Angelica Francesca; Ponio, Jesito Jr; Quizon, Jeannie; Sibal, Maria Elisa Andrea
Pampanga, a predominantly agriculture province, is currently undergoing land conversions or reclassification of agricultural lands to non-agricultural uses such as residential, commercial, and industrial areas. This research was conducted to identify the effects, if any, of land conversion to the agricultural economy of Pampanga. To make an in-depth analysis of the subject, the group studied the agricultural situations of San Fernando, Mexico, and Mabalacat as its case study. The researchers also made use of qualitative and quantitative measures, such as interviews, questionnaires, and regression analysis, to prove or disprove their hypothesis that land conversion will bring about a decline in the agricultural sector. Questionnaires were distributed and interviews were conducted on a number of farmers within the area of study in order to obtain their observations and opinions on the land conversion activities and the agricultural sector as a whole. As for the quantitative analysis, the nominal income of the farmers in palay production, used as the determinant of the level of agricultural economy, was treated as the dependent variable of the regression model; while the presence of adjacent land conversions, cavans of palay produced, hectares of land owned, and the average farmgate price of palay are the model's independent variables. With regard to the responses of the interviewed farmers, it can be inferred that there has been a significant decline of interest in farming activities within the last 10 years; with the lack of financial assistance and the unjust farmgate prices of their crops as their main reasons. These findings were supported by the outcome of the regression procedure, as the independent variables were found to be significant variable in the model, the volume of palay produced in cavans, does not fully explain the changes in the dependent variable, as indicated in the level of R2 which is .4398. The group then concluded that land conversion in fact affects the level of an area's agricultural economy, but it does not mean that it automatically leads to its decline, as other factors that are not included in the model can also affect the locale's agricultural sector. As for the group's recommendation, it pointed out the importance of efficient financial assistance programs, like lowering the interest rate of agriculture-related loans by providing subsidies to the cost of seeds and fertilizers as an example. With this, the agricultural sector can be more competitive, which will benefit the country as a whole.